First mantis shrimp of the genus Pullosquilla Manning, 1978, from Vanuatu (Crustacea: Stomatopoda: Nannosquillidae), with a key to the species - Ahyong, Shane T. (Zootaxa, 2025)
The diminuative nannosquillid mantis shrimps of the genus Pullosquilla Manning, 1978, live in sand burrows on Indo-West Pacific coral reefs. The present study describes the fifth species of Pullosquilla, collected from Vanuatu. The new species most closely resembles P. malayensis (Manning, 1968) and P. litoralis (Michel & Manning, 1971) and differs from other congeners in ornamentation of the telson and structure of the uropodal protopod. A key to the species of Pullosquilla is provided.